Samfundsøkonomi og lufthavnsinvesteringer - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
– The focus is effects of investments in airports and runways on the market for air travel and more in general for the production possibilities of the economy. In the case of Greenland two types of impacts can be sorted out. One is more efficient production of air transport due to increased density in the utilization of the net because of no use or less use of the airport in Kangerlussuaq. The other effect, connected to the first, is that resources are set free by avoidance of double work receiving the same passengers (and goods) in Kangerlussuaq and especially in Nuuk. Transformation curves are used to illustrate both effects and the first is dealt with also in an ordinary price quantity diagram. Using previous calculations and estimates done by the author two specific scenarios are treated in the theoretical framework presented: one is a lengthening of the runway in Nuuk to 1799 m and less intensive use of Kangerlussuaq, the other is the building of an airport south of Nuuk with a 3000 m runway in combination with abandoning Kangerlussuaq. Profitability and amortisation of the investments are reviewed in transformation curve diagrams. On the assumptions of the calculations both scenarios are profitable, but by far the most profitable is the big investment south of Nuuk. Concluding remarks stress the preliminary character of my calculations, but they also point out that decision makers' choice of scenarios to be discussed and compared is unstable.
hdl:10398/7500
Keywords: H00; 330